2019
DOI: 10.1108/ijoem-11-2017-0457
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of capital formation and foreign aid nexus in Nigeria

Abstract: Purpose The issue of foreign aid has continued to gain renewed economic cum political attention in the early years of the twenty-first century. At a summit, popularly known as the Millennium Summit, which took place in 2000, there was an agreement by the international community concerning some goals known as the Millennium Development Goals which were targeted to be reached by the year 2015 but have now been replaced by the Sustainable Development Goals. Against this background, it becomes pertinent to ascerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Hansen and Tarp (1999) examined the effect of aid inflows on the growth rate of GDP per capita in developing countries. The findings showed that aid is positively associated with both growth and capital formation (see also Martínez-zarzoso, 2019; 348 IJOEM 15,2 Tang and Bundhoo, 2017;Karras, 2006;Mustafa et al, 2018;Yiew and Lau, 2018;Orji et al, 2019). In a related study on the SSA, Clemens et al (2004) contended that aid has a statistically significant impact on real per capita growth.…”
Section: Empirical Reviewmentioning
confidence: 98%
“…Hansen and Tarp (1999) examined the effect of aid inflows on the growth rate of GDP per capita in developing countries. The findings showed that aid is positively associated with both growth and capital formation (see also Martínez-zarzoso, 2019; 348 IJOEM 15,2 Tang and Bundhoo, 2017;Karras, 2006;Mustafa et al, 2018;Yiew and Lau, 2018;Orji et al, 2019). In a related study on the SSA, Clemens et al (2004) contended that aid has a statistically significant impact on real per capita growth.…”
Section: Empirical Reviewmentioning
confidence: 98%
“…Taking seven middle-income countries of South and South-East Asia, Sharma and Kautish (2019) exposed that aid policy interaction has a significant and positive impact on economic growth in this region. Orji et al, (2019) revealed that foreign Aid has a positive and significant effect on capital formation in Nigeria. Similar results were obtained by Yahyaoui and Bouchoucha (2019) for Tunisia, Chirwa and Odhiambo (2019) for Zambia, Mehmood and Seror (2019) for Pakistan, Bhattarai (2009) for Nepal, Sakyi (2011) for Ghana, Rao et al, (2020) for South-East Asia and South Asian countries.…”
Section: Brief Review Of the Literaturementioning
confidence: 99%
“…In this study, we are going to reveal the effect of FA on the Economic growth of Bangladesh. The theoretical foundation of our research would be based on the two-gap model (Orji et al, 2019).…”
Section: Theoretical Framework and Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations